2019
DOI: 10.1108/ijppm-03-2018-0108
|View full text |Cite
|
Sign up to set email alerts
|

Does job embeddedness predict turnover intentions in SMEs?

Abstract: Purpose There is an absence of research examining job embeddedness in SMEs. Results of job embeddedness studies may not apply to SMEs, because the process of managing a SME differs from that of the large firm. The purpose of this paper is to examine relationships between on-the-job embeddedness, as well as each of its sub-dimensions, and turnover intentions; and group cohesion, on-the-job embeddedness and turnover intentions. Design/methodology/approach Data were collected from 147 employees in SMEs located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 100 publications
(203 reference statements)
4
55
0
4
Order By: Relevance
“…The result can be concluded that there is a negative correlation between job embeddedness and voluntary turnover. This is consistent with the study stated that there was a negative and significant relationship between job embeddedness and voluntary turnover (Afsar et al, 2018;Dechawatanapaisal, 2018;Coetzer et al, 2019). Karatepe and Ngeche (2012) studied about job embeddedness, turnover intention and job performance.…”
Section: Relationship Between Job Embeddedness and Voluntary Turnoversupporting
confidence: 89%
“…The result can be concluded that there is a negative correlation between job embeddedness and voluntary turnover. This is consistent with the study stated that there was a negative and significant relationship between job embeddedness and voluntary turnover (Afsar et al, 2018;Dechawatanapaisal, 2018;Coetzer et al, 2019). Karatepe and Ngeche (2012) studied about job embeddedness, turnover intention and job performance.…”
Section: Relationship Between Job Embeddedness and Voluntary Turnoversupporting
confidence: 89%
“…This study considered two possible moderators in the measurement model. In addition, the study can be expanded to find the influence of other potential moderating factors, such as commuting time, financial requirements and working group cohesion as recommended by Zhang et al (2012) and Coetzer et al (2019).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Recently, the strong relevance of job embeddedness and turnover intentions was clearly highlighted by Afsar et al's [32] work, which suggested that job embeddedness fully mediates the relationship between high-performance work practices and turnover intentions. The latest research of Coetzer et al [33] showed that on-the-job embeddedness and each sub-dimension were negatively related to turnover intentions in small and medium enterprises.…”
Section: Job Embeddedness Job Satisfaction Affective Commitment Andmentioning
confidence: 99%